The effect of interferon alpha administration on cytokine levels in sheep - Devran Coşkun; Merve İder; Mustafa Sedat Arslan; Rahmi Canbar; Enver Yazar (Eurasian Journal of Veterinary Sciences, 2020)
Aim: The primary aim of this study was to determine the effect of parenteral recombinant human interferon (rHuIFN)-?2a administration on serum tumor necrosis factor (TNF)-?, interleukin (IL)-6 and IL-10 levels in healthy sheep. In addition, the main physiological parameters (rectal temperature, pulse rate, respiratory rate), hemogram and blood gas parameters were determined, as well. Materials and Methods: In this study, 9.000.000 IU rHuIFN-?2a was administered subcutaneously in 10 Merinos sheep. Blood samples were taken before (0 hours) and after at 4, 8, 12, 24, 48, 72, 96 and 120 hours. Rectal temperature, pulse and respiratory rate were also determined at the same sampling times. Sheep-specific TNF-?, IL-6 and IL-10 levels were determined from serum samples by the ELISA reader. Hemogram and blood gas parameters were measured by complete blood cell counter and blood gas analyzer, respectively. Results: After rHuIFN-?2a treatment, TNF-? and IL-10 concentrations reached peak levels (p<0.05) at the 96 hours, whereas the IL-6 level did not change in a statistically significant (p>0.05). On the other hand, a temporary increase in rectal temperature and pO2 levels (p<0.05) were determined, while decreased potassium and ionized calcium levels (p<0.05) were measured. Statistically significantly (p<0.05) fluctuations were determined in pulse rate, white blood cell counts, pH, base(ecf) and sodium values. Conclusion: It may be stated that administration of rHuIFN-?2a showed immunological effects in sheep, as it is generally accepted as safe and can be considered for use in treatment.